Non-targeted HIV testing in the emergency department: not just how but where. Issue 12 (2nd December 2018) - Tan, Rainer; Hugli, Olivier; Cavassini, Matthias; Darling, Katharine
ABSTRACT: Introduction : The emergency department (ED) has the potential to enhance early HIV diagnosis through HIV testing programs. How these are implemented is a subject of debate. Areas covered : We describe the main HIV testing approaches: diagnostic testing, targeted screening, and non-targeted screening, and review ED-based non-targeted HIV screening studies conducted after 2006 among ≥5000 patients. As well as examining how testing is offered, we focus on where it is offered, through the patient's journey from registration, via triage and the waiting room, to the bedside. Barriers to the testing offer, acceptance and performance were examined at each location. While testing offer rates were higher at registration and triage, compared to the waiting room and bedside, this was sometimes at the expense of testing acceptance and performance. Variables affecting testing rates included type of consent, employment of external staff and type of testing: fourth generation serological testing versus rapid testing. Expert commentary : These large studies shed light on the importance of where as well as how HIV testing is performed, and the ways in which the 'where' can influence non-targeted screening yields. This perspective enables testing approaches to be tailored to specific ED settings in order to maximize testing rates.